Sepsis-Exacerbated Brain Dysfunction After Intracerebral Hemorrhage - Lin, Jie; Tan, Binbin; Li, Yuhong; Feng, Hua; Chen, Yujie (Frontiers in Cellular Neuroscience, 2022)
Sepsis susceptibility is significantly increased in patients with intracerebral hemorrhage (ICH), owing to immunosuppression and intestinal microbiota dysbiosis. To date, ICH with sepsis occurrence is still difficult for clinicians to deal with, and the mortality, as well as long-term cognitive disability, is still increasing. Actually, intracerebral hemorrhage and sepsis are mutually exacerbated via similar pathophysiological mechanisms, mainly consisting of systemic inflammation and circulatory dysfunction. The main consequence of these two processes is neural dysfunction and multiple organ damages, notably, via oxidative stress and neurotoxic mediation under the mediation of central nervous system activation and blood-brain barrier disruption. Besides, the comorbidity-induced multiple organ damages will produce numerous damage-associated molecular patterns and consequently exacerbate the severity of the disease. At present, the prospective views are about operating artificial restriction for the peripheral immune system and achieving cross-tolerance among organs via altering immune cell composition to reduce inflammatory damage.